2006
DOI: 10.1177/1082013206060445
|View full text |Cite
|
Sign up to set email alerts
|

Note. Behaviour of a Mixture of Acacia glomerosa, Enterolobium cyclocarpum and Hymenaea courbaryl Gums in Ice Cream Preparation

Abstract: A mixture of gums from Acacia glomerosa, Enterolobium cyclocarpum and Hymenaea courbaril were tested as stabilisers in the preparation of ice cream. Quality characteristics of the product (viscosity, overrun (OR), FE, meltdown, shape factor and sensory properties) were determined. These characteristics were compared with those exhibited for products obtained with a mixture of commercial gums. The mixture tested provided suitable viscosity for ice creams with the corresponding OR and texture. It gave better foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…Also, frozen ice cream containing 0.05% GG or 0.025% CSM gained the highest score, which characterized with more smoothness and creaminess compared with other treatments. These results are agreement with those reported by Rincon et al (2006) and BahramParvar et al (2010). The improvement in melting quality and body and texture could be attributed to the increase in viscosity and/or overrun, which inhibits the development of iciness in frozen ice cream (Schmidt and Smith, 1992) and melted relatively slowly in the mouth (Ohmes et al, 1998;Baer et al, 1999).…”
Section: Meltdown Of Frozen Ice Creamsupporting
confidence: 92%
“…Also, frozen ice cream containing 0.05% GG or 0.025% CSM gained the highest score, which characterized with more smoothness and creaminess compared with other treatments. These results are agreement with those reported by Rincon et al (2006) and BahramParvar et al (2010). The improvement in melting quality and body and texture could be attributed to the increase in viscosity and/or overrun, which inhibits the development of iciness in frozen ice cream (Schmidt and Smith, 1992) and melted relatively slowly in the mouth (Ohmes et al, 1998;Baer et al, 1999).…”
Section: Meltdown Of Frozen Ice Creamsupporting
confidence: 92%
“…Acacia glomerosa , Enterolobium cyclocarpum and Hymenaea courbaril are species grown in Venezuela that yield gums. The mixture of the above gums produced a viscosity of 0.040 Pa.s in ice cream mixes, which was higher than the viscosity of a mixture of commercial gums (0.035 ± 0.0012 × 10 −3 Pa.s), while the viscosity of samples without stabiliser was found to be 0.014 ± 0.0012 × 10 −3 Pa.s (Rincon et al. 2006).…”
Section: Resultsmentioning
confidence: 95%
“…They showed that ice cream produced using only the salep extract had significantly (P < 0.05) lower resistance to melting than those produced with the stabiliser combinations. Rincon et al (2006) also found the meltdown of ice creams to be 65 ± 2.11%, 5 ± 1.03% and 40 ± 1.02% for samples without stabilisers, with mixtures of commercial gums and mixture of local gums, respectively. This latter research showed that the mixture of local Venezuela gums provided desirable melting characteristics, as was demonstrated by the tendency to reduce the rate of melting down.…”
Section: Melting Resistancementioning
confidence: 84%
“…The overrun values determined in this study were within these limits, with the exception of samples E, F and G. Rincon et al . () reported that the strongest levels of overrun were determined in ice cream samples produced using the mixture of the gums from Acacia glomerosa , Enterolobium cyclocarpum and Hymenaea courbaril and mixture of commercial gums compared with the control samples (without stabilisers).…”
Section: Resultsmentioning
confidence: 99%